Brain 18F-FDG PET in Cowden Syndrome. (February 2022) - Grangeret, Justine; Frismand, Solene; Muller, Marie; Renaud, Mathilde; Verger, Antoine
Abstract : Abstract: Cowden disease is associated with neurodevelopmental abnormalities such as macrocephaly, autism spectrum disorder, and developmental delay. Our understanding of neuroimaging anomalies in patients with PTEN mutations is limited to anatomical MRI abnormalities including white matter abnormalities, meningiomas, arteriovenous malformations, and cortical dysplasia. Our current communication extends the neurological Cowden syndrome phenotype by using brain 18 F-FDG PET/CT imaging as a useful complementary approach to MRI to explore movement disorders and neuropsychiatric syndromes in a patient with Cowden disease. Brain 18 F-FDG PET/CT showed diffuse hypometabolism of the prefrontal mesial and dorsolateral areas including supplementary motor areas, the pons extended to the cerebellum.